2014
DOI: 10.1007/s10470-014-0350-9
|View full text |Cite
|
Sign up to set email alerts
|

Design and analysis of high speed capacitive pipeline DACs

Abstract: Abstract-Design of a high speed capacitive digital-to-analog converter (SC DAC) is presented for 65 nm CMOS technology. SC pipeline architecture is used followed by an output driver. For GHz frequency operation with output voltage swing suitable for wireless applications (300 mVpp) the DAC performance is shown to be limited by the clock feed-through and settling effects in the SC array rather than by the capacitor mismatch or kT/C noise, which appear negligible in this application. While it is possible to desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…In order to meet the kT/C noise requirements, a large capacitor is required for the holdoperation, which limits speed. Moreover, based on the earlier study we have found that the pipeline capacitor array suffers from clock feed-through effect for high-resolution (12-bit) DACs [12]. Fig.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…In order to meet the kT/C noise requirements, a large capacitor is required for the holdoperation, which limits speed. Moreover, based on the earlier study we have found that the pipeline capacitor array suffers from clock feed-through effect for high-resolution (12-bit) DACs [12]. Fig.…”
Section: Introductionmentioning
confidence: 89%
“…B. Capacitor mismatch Similar to the capacitor mismatch analysis in [12] the standard variation of VDNL is described as…”
Section: ) Noise Due To All Binary and Thermometer Sc Arraysmentioning
confidence: 99%
See 3 more Smart Citations